Temperature response of photosynthetic light‐ and carbon‐use characteristics in the red seaweed Gracilariopsis lemaneiformis (Gracilariales, Rhodophyta). Issue 2 (11th March 2014) - Zou, Dinghui; Gao, Kunshan; Harley, C.
<x xml:space="preserve">Abstract</x> The red seaweed Gracilariopsis is an important crop extensively cultivated in China for high‐quality raw agar. In the cultivation site at Nanao Island, Shantou, China, G. lemaneiformis experiences high variability in environmental conditions like seawater temperature. In this study, G. lemaneiformis was cultured at 12, 19, or 26°C for 3 weeks, to examine its photosynthetic acclimation to changing temperature. Growth rates were highest in G. lemaneiformis thalli grown at 19°C, and were reduced with either decreased or increased temperature. The irradiance‐saturated rate of photosynthesis (Pmax) decreased with decreasing temperature, but increased significantly with prolonged cultivation at lower temperatures, indicating the potential for photosynthesis acclimation to lower temperature. Moreover, Pmax increased with increasing temperature ( 30 μmol O2 · g−1FW · h−1 at 12°C to 70 μmol O2 · g−1FW · h−1 at 26°C). The irradiance compensation point for photosynthesis (Ic) decreased significantly with increasing temperature (28 μmol photons · m−2 · s−1 at high temperature vs. 38 μmol photons · m−2 · s−1 at low temperature). Both the photosynthetic light‐ and carbon‐use efficiencies increased with increasing growth or temperatures (from 12°C to 26°C). The results suggested that the thermal acclimation of photosynthetic performance of G. lemaneiformis would have important ecophysiological implications in sea cultivation for improving photosynthesis at low temperature and maintaining high standing biomass during summer. Ongoing climate change (increasing atmospheric CO2 and global warming) may enhance biomass production in G. lemaneiformis mariculture through the improved photosynthetic performances in response to increasing temperature.